2019
DOI: 10.4171/rmi/1142
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Khovanov spectra

Abstract: We prove that the spectrum constructed by González-Meneses, Manchón and the second author is stably homotopy equivalent to the Khovanov spectrum of Lipshitz and Sarkar at its extreme quantum grading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Shortly after, another geometric realization of the (minimal) extreme Khovanov homology was given [GMS18] in terms of an independence simplicial complex constructed from the link diagram. This construction was later shown to coincide with the one of Lipshitz and Sarkar [CMS20] as follows: functors from the cube to the Burnside 2-category can be understood as generalizations of simplicial complexes; such a functor is a simplicial complex if it factors through the category of sets and takes values on singletons and the empty set.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Shortly after, another geometric realization of the (minimal) extreme Khovanov homology was given [GMS18] in terms of an independence simplicial complex constructed from the link diagram. This construction was later shown to coincide with the one of Lipshitz and Sarkar [CMS20] as follows: functors from the cube to the Burnside 2-category can be understood as generalizations of simplicial complexes; such a functor is a simplicial complex if it factors through the category of sets and takes values on singletons and the empty set.…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, in [CMS20] the authors showed that if a cube F : 2 n → B factors through some functor F : Remark 3.6. The spectrum Tot F is denoted |F | in [LLS20].…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Independently, in [GMS] it was introduced a method to associate to every link diagram D a simplicial complex I D so that its cohomology equals Khovanov homology of D at extreme quantum grading. This construction was proven to be equivalent to that of Lipshitz and Sarkar in extreme quantum grading [CS1]. The following conjecture was formulated in [PS1].…”
mentioning
confidence: 87%
“…Lipshitz and Sarkar constructed a Z-graded family of spectra X j (D)) associated to a link diagram D, and they proved that for each j ∈ Z, the stable homotopy type of the spectrum X j (D)) is a link invariant up to stable homotopy and there is a canonical isomorphism H * (X j (D)) ∼ = Kh * ,j (D) [5]. Morán and Silvero [6] later proved that X D is stably homotopy equivalent to the Khovanov spectrum of Lipshitz and Sarkar at its extreme quantum grading. Our proof uses combinatorial structures of a bipartite circle graph.…”
Section: Introductionmentioning
confidence: 99%